Study on the Contour Design of Disc Cam with Offset Translation Pushrod based on Solid Works and Matlab - Liu Xueshen; Wang Zhen; Ai Zetan; Jiang Zhiqiang (Jixie chuandong)
The traditional methods of designing cam profile always leads to complicated calculation,low computational accuracy and efficiency. But by using Matlab programming language,the computational accuracy can be increased and the design period can be shortened in the process of solving and drawing cam profile.Firstly,the data points on the curve that are drawn in the Matlab can be derived. Secondly,a rough draft of cam profile is generated in Solid Works. Finally,the three- dimensional model of cam profile is created during the stretching process. This method is easy to operate and can greatly improve the design efficiency by quickly modifying the shape of cam profile according to the actual working conditions.